Corak Pemikiran Hermeneutika Al-Qur’an Prof. Sahiron Syamsuddin - Muhamad Ridwan Syafi'i (Jurnal Budi Pekerti Agama Islam, 2024)
This research aims to explore the hermeneutical thought patterns of the Koran; Prof. Sahiron Syamsuddin uses descriptive qualitative methods with literature analysis. The research results show that the ma'na-cum-maghza hermeneutic method developed by Prof. Sahiron Syamsuddin is a development of various previous interpretive theories with no genuinely new elements. The proposed methodology must be more thorough, and the solutions and proposals are still general and ambiguous. Criticism of classical ulama's thinking is more dominant, and the absence of the word "Hermeneutical Tafsir of the Koran" shows that this method is impractical and can only be applied in a limited way. The implication is that this hermeneutics is unsuitable for studying the Koran because it can cause confusion and doubt. This approach is based on an attitude of skepticism and relativism, which places the Koranic text on par with other texts, resulting in uncertainty in meaning and interpretation that is relative and temporary. The use of the ma'na-cum-maghza hermeneutic method can result in the deconstruction of Islamic laws in the Koran and disrupt the structure of Islamic epistemology.